Models, Metaphors and Symbols for Information and Knowledge Systems - David Williams (Journal of Entrepreneurship, Management and Innovation)

(untitled)
A literature search indicates that Data, Information and Knowledge continue to be placed into a hierarchical construct where it is considered that information is more valuable than data and that information can be processed into becoming precious knowledge. Wisdom continues to be added to the model to further confuse the issue. This model constrains our ability to think more logically about how and why we develop knowledge management systems to support and enhance knowledge- intensive processes, tasks or projects. This paper seeks to summarise development of the Data-Information-Knowledge-Wisdom hierarchy, explore the extensive criticism of it and present a more logical (and accurate) construct for the elements of intellectual capital when developing and managing Knowledge Management Systems.